Procesos críticos entre arte y sociedad - Arellano Salvatierra, Pamela Elizabet (2016)
The urban regeneration in Machala is a process of urban transformation that without improves the visual aspect of the city, it has been a process that has not considered certain stories that characterized the place of intervention, that is why we see theme parks that Do not represent the site, that is why this artistic research focuses on these urban changes that do not contribute to the cultural identity of the Machaleños and therefore from the artistic intervention is proceeded to make a criticism of public institutions who are in charge In building works without a previous census. The present research work on the artistic intervention as enhancer of culture and identity of the city of Machala, shows the technical processes as far as the related to the artistic interventions, the same that are developed in the public spaces. From our proposal we try to create awareness about the collective the good use of the public spaces destined to the culture and therefore to enhance our identity. The artistic interventions allow us to improve the visibility oriented to the culture and identity of our city, and addresses the problematic about these public spaces of urban regeneration in the periphery of our city that, with the remodeling, is losing part of the heritage that identified us , We are talking about the natural areas of the mangrove, that was in certain sectors. The research seeks to rethink about the transformation undergone in nature by the society that have ended with the cultural part disappearing the natural environment of the mangroves that are very important.